EVALUATION OF STRATEGIC PLANS - Handayani, Anita; Zamroni, Zamroni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Evaluation of strategic plans also helps organizations identify obstacles faced during implementation, analyze discrepancies between plans and achievements, and provide input for future improvements. The purpose of this article is to explain the definition and basic concepts of strategic plan evaluation, analyze the effectiveness of implementing strategic plans in achieving organizational goals to assess the extent to which the strategies implemented have succeeded in achieving the expected targets. Identifying obstacles in implementing strategic plans and their impact on achieving organizational goals to understand the factors that hinder success and their negative impact on organizational goals. Assess the relevance of strategic plans that have been prepared in facing changes in the external environment to ensure existing strategies remain appropriate to the situation and needs that continue to develop. Determining the most appropriate evaluation method or approach. This process ensures that the strategy remains relevant in facing the dynamics of change in both the internal and external environment. Ultimately, strategic plan evaluation serves as a continuous learning and development tool for the organization. Evaluation of educational strategic plans is an essential step that allows educational institutions to assess the effectiveness of strategies that have been implemented and ensure optimal achievement of educational goals. Through this evaluation, related parties can identify successes and correct weaknesses in strategy implementation, so that future planning can be more relevant and responsive to student needs and existing challenges